Postwar Justice in Bosnia and Herzegovina - Kutnjak Ivković, Sanja (International criminal justice review, 2021)
This article explores the perceptions of justice expressed by victims of severe violations of human rights in Bosnia and Herzegovina (BiH) who have testified before the International Criminal Tribunal for the former Yugoslavia (ICTY) and/or the Court of BiH. In 2009, we surveyed 495 members of a victims’ association and inquired about their perceptions of postwar justice. The respondents were more likely to assess the ICTY than the Court of BiH as fair both in terms of its decisions and procedures. Compared to the perceptions of procedural justice, perceptions of distributive justice were more strongly correlated with the assessments of both courts’ overall fairness. Multivariate logistic regression models reveal that measures of procedural justice are directly related to the respondents’ evaluations of the both courts’ fairness, while demographic factors were mostly unrelated to their evaluations of the two courts. The results of our study suggest that the respondents who said that they testified at the ICTY had more positive views about both the ICTY and the Court of BiH than the respondents who said that they either testified at both courts or only at the Court of BiH.